Differences between all-around results in women`s artistic gymnastics and ways of minimizing them - Atikovic, A.; Kamenjaševic, E.; Nožinovic Mujanovic, A.; Užicanin, E.; Tabakovic, M.; Curic, M. (Baltic Journal of Health and Physical Activity, 2020)
Background: In the present study, the main goal was to establish whether the disciplines are equal and should the Code of Points (COP) women's artistic gymnastics be revised in terms of point standardization on apparatus. Material and methods: The sample included all-around senior female gymnasts who participated in the qualification (C-I) competitions at World Championships held in 2009-2019. Results: The biggest differences are even two points between the two apparatus vault and balance beam. Vault compared to other apparatus is different for 1.559 points. Presentation of correlations between each apparatus the evidence that nothing has changed significantly in recent years, whereas correlations of the difficulty values of elements are extremely high between the present COP. Conclusions: With this analysis, we have found that the results achieved at the vault and other apparatus were significantly different in terms of success in all-around competition.